The Human Cost of Recessions : Assessing It, Reducing It - Dao, Mai (IMF Staff Position Notes; Staff Position Note ;, 2010)
Recessions leave scars on the labor market. Over 200 million people across the globe are estimated to be unemployed at present resulting from the Great Recession of 2007-09. We assess the human cost of increased unemployment by surveying what is known about the effects of past recessions. If past is prologue, the cost to the unemployed (and society) could be high. The focus of this paper is on advanced economies. To their credit, most countries mounted strong policy responses to minimize the human costs, and the policy actions were notable also for their consistency and coherence across countries.